Comparative evaluation of genotoxicity induced by nitrofurazone in two ciliated protozoa by detecting DNA strand breaks and DNA–protein crosslinks. (July 2015) - Hong, Yazhen; Lin, Xiaofeng; Cui, Xudong; Zhou, Liang; Al-Rasheid, Khaled A.S.; Li, Jiqiu
Highlights: Importance of organism specific factors was considered in selecting model organisms. Nitrofurazone-induced genotoxicity was evaluated by DNA damage in two ciliates. Interspecific differences occurred in LD50 and parameters for measuring DNA damage. Genotoxicity parameters showed biphasic dose–response to nitrofurazone dose. Nitrofurazone-induced genotoxicity and organism-specific factor were confirmed. Abstract: Although organism-specific factors related to individual indicator organisms have hampered the use of bioassays for the evaluation of environmental risk in practice, the importance of understanding organism-specific factors when selecting model organisms has also not yet been fully recognized. In this work, genotoxicity was evaluated in the ciliated protozoa, Euplotes vannus and Pseudokeronopsis rubra, when exposed to graded doses of nitrofurazone for several discrete durations. Genotoxicity was expressed based on the LD50 and was determined by assessing DNA strand breaks (through alkaline comet assay) and DNA–protein crosslinks (DPCs), by means of a KCl–SDS precipitation assay. It was found that E. vannus generally had lower LD50 's than P. rubra ( P  < 0.05), and that the LD50 values decreased in both ciliates as the exposure durations increased. Compared to the control groups, the nitrofurazone treated E. vannus generally produced more DNA strand breaks ( P  < 0.05), but for DPCs ( P  > 0.05). The relationship between these parameters was reversed in the case of P. rubra . Biphasic dose–response relationships were generally detected between nitrofurazone and genotoxicity parameters, however, parameters for DNA strand breaks presented significantly positive correlations between each other ( P  < 0.05), but showed nearly no significant correlations with DPC induction. In brief, our findings confirmed nitrofurazone-induced genotoxicity and the important role of organism-specific factors in the selection of model organisms from ciliated protozoa for environmental monitoring and risk assessment in aquaculture.